Citrulline activates adenosine receptors: New insight into metabolic pathways interaction - Soloviev, Anatoly; Kozlowsky, Vadym; Sydorenko, Vadym; Ivanova, Irina; Samofalova, Dariia; Fetyukhin, Vladimir (Biochemical pharmacology, 2024)
Citrulline is a non-proteinogenic amino acid that forms as by-product in nitric oxide (NO) synthesis from arginine and may act in concert with NO as an independent signaling molecule that involves in the mechanism of vascular smooth muscle vasodilation. In this study we examined the effects of citrulline on pulmonary artery smooth muscles. Experimental design comprised outward potassium currents measurements in enzymatically isolated rat pulmonary artery smooth muscle (PASMc) cells using whole-cell patch clamp technique, isometric contractile force recordings on rat pulmonary artery rings and method of molecular docking simulation. Citrulline in a concentration 10-9-10-5 M relaxed phenylephrine (PHE)-preactivated SM of rat pulmonary artery in a dose-dependent manner (EC50 0,67 μM). This citrulline-induced relaxation was dependent on an intact endothelium. Bath application of citrulline (10-8-10-5 M) on isolated PASMc induced a significant increase in the amplitude of outward potassium current (Ik). The adenosine antagonist caffeine (10-6 M) effectively blocked both the citrulline-induced relaxation response and Ik increment. Molecular docking modeling suggests that caffeine blocking the potent activity of citrulline results from competitive interactions at the A2 adenosine receptor binding site. In summary, our data suggest that citrulline, released with NO at low concentrations, can effectively interact with adenosine receptors in smooth muscle cells, causing their relaxation, indicating surprising interaction between NO and adenosine pathways.
Keywords: Animals; Vascular smooth muscle; vztah mezi dávkou a účinkem léčiva; Rats, Wistar; arteria pulmonalis; Receptors, Purinergic P1; simulace molekulového dockingu; Caffeine; Muscle, Smooth, Vascular; Pulmonary Artery; purinergní receptory P1; Citrulline; Dose-Response Relationship, Drug; Male; citrulin; svaly hladké cévní; krysa rodu Rattus; mužské pohlaví; zvířata; Nitric oxide; Rats; Molecular Docking Simulation; Endothelium; potkani Wistar; Adenosine receptors